Urinary and synovial pyridinium crosslink concentrations in patients with rheumatoid arthritis and osteoarthritis. Issue 2 (February 1995) - Sinigaglia, L; Varenna, M; Binelli, L; Bartucci, F; Arrigoni, M; Ferrara, R; Abbiati, G
Abstract : OBJECTIVES--To assess urinary and synovial concentrations of hydroxypyridinium crosslinks of collagen in patients with rheumatoid arthritis (RA) and osteoarthritis (OA) and to evaluate whether a combined measurement in the two compartments could give additional information about the origin of these compounds in joint diseases. METHODS--Concentrations of hydroxypyridinoline (HP) and lysylpyridinoline (LP) were measured by high pressure liquid chromatography in urinary and synovial samples collected from 20 patients with RA and 20 patients with knee OA. Full laboratory and clinical assessments were performed. RESULTS--Urinary concentrations of both HP and LP were significantly greater in RA than in OA. Urinary HP in RA correlated with the number of swollen joints corrected for Lansbury index and with erythrocyte sedimentation rate and C reactive protein. In synovial fluid from both groups, only relatively small amounts of HP were measured, while bone type I collagen specific LP was below the limit of detection in all samples. In RA patients, but not in OA patients, there was a strong correlation between urinary and synovial concentrations of HP (r = 0.75). CONCLUSIONS--The results underline the relationship between urinary HP and disease extent and activity in RA. The findings in synovial fluid support the hypothesis of an extraskeletal origin of HP in chronic joint diseases in which cartilage and synovial turnover may be increased.